Using Grid Search and Guided Random Search (Simulated Annealing) Methods in Determining the Earthquake Hypocenter in the Majalengka Region, West Java on November 11, 2021: Penggunaan Metode Grid Search dengan Guided Random Search (Simulated Annealing) dalam Menentukan Hiposenter Gempa Bumi Daerah Majalengka, Jawa Barat pada 11 November 2021 - Fachri Aldi Pramudya; Restu Ningsih; Hayu Nurfaidah; Siska Erna Sephiana; Rahmat Catur Wibowo; Ahmad Zaenudin (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2023)
Tectonic earthquakes are generally caused by the release of energy produced by a pressure from a moving slab. This study aimed to test the use of grid search methods and guided random search in determining the hypocenter position of the earthquake in the case of the Majalengka regional earthquake, West Java which occurred on November 11, 2021. In this study used earthquake source data with the number of 5 stations, are COCO, KAPI, PALK, MBWA, and NWAO which can be accessed on the IRIS. From the results of determining the earthquake hypocenter using the grid search method, the position of the earthquake hypocenter is obtained with a latitude position of 6.596861oS and for a longitude position of 108.2871°E with a depth of 200 km, while from the processing of the simulated annealing method, the latitude position is 6.501645°S and longitude 108.2252°E with depth of 172.1 km. Meanwhile, if we compare the position of the earthquake hypocenter according to IRIS, are the latitude position of 6.6027°S and for the longitude position of 108.105°E with a depth of 164.41 km, because the hypocenter data from IRIS has been revised by a seismologist so that it is used as a reference, the results that are closest to the position according to IRIS are the results of the simulated annealing method.